Konstruksi Media Pemberitaan Bunuh Diri di Gorontalo (Analisis Framing pada Media Daring Hargo.co.id dan Dulohupa.id) - Nurnadela Rahmat; Noval Sufriyanto Talani; Muhammad Akram Mursalim (Jambura Jurnal Ilmu Komunikasi, 2025)
This study analyzes the construction of events and framing in the reporting of suicide cases in Gorontalo in 2023 on the online media Hargo.co.id and Dulohupa.id. Using a qualitative descriptive approach with the theoretical framework of Zhongdang Pan & Gerald M. Kosicki (syntax, script, thematic, and rhetoric). The researcher acted as the main instrument in the study, with data obtained through documentation and literature review. The results show that both media construct suicide as a simple, individual, tragic, dramatic, and sensational actual event. Hargo.co.id also presents suicide as an impulsive act with an emphasis on moral values. Six forms of framing were found: incidental framing, personal tragedy, recurring patterns, moral judgment, victim exploitation, and passive framing.